Lower percentages of T regulatory cells in children with type 1 diabetes - preliminary report - Marek Hryszko; Mirosława Urban; Bożena Florys; Remigiusz Urban; Anna Stasiak-Barmuta; Włodzimierz Łuczyński (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction:Type 1 diabetes (T1D) isa well-known autoimmune disease, however there are still some processes in its pathogenesis to be elucidated. In the last few years the role of T regulatory cells in the pathogenesis of T1D has been investigated. The aim of study was to determine the percentages and numbers of T regulatory cells in the peripheral blood of children with type 1 diabetes. Material and methods: A total of 25 children with newly diagnosed type 1 diabetes were studied, and compared to the control group consisted of 30 healthy children with no signs of autoimmune, chronic, inflammatory, neoplastic disease, and no evidence ofT1D in their families. Flow cytometric analysis ofT-cell subpopulations was performed using thefollowing markers: anti-CD3, anti-CD4, anti-CD25, and anti-CD127 (IL-7R). Results: In the group of children with type 1 diabetes we noted statistically significant lower percentages of T regulatory cells, i.e., CD4+CD25 high and CD4+CD127 low comparing to the control children. There were no differences in other assessed parameters: white blood cell count, lymphocytes, CD4+ and CD4+CD25 high CD127 low cells (percentage and count). We did not find the correlation between patients' age and any of analysed parameters. Conclusions: Our results suggestthe lower percentages ofTregs in children with T1D, however those data need to beconfirmed in a larger cohort of patients and complemented with functional studies, e.g. at mRNA level. In our opinion T regulatory cells could be excellent candidates for cell therapy in newly diagnosed type 1 diabetic children.